Genome resequencing data for Iranian local dogs and wolves - Zeinab Amiri Ghanatsaman; Guo-Dong Wang; Masood Asadi Fozi; Ya-Ping Zhang; Ali Esmailizadeh (BMC Research Notes, 2020)
Abstract Objective The data provided herein represent the whole-genome resequencing data related to three wolves and three Iranian local dogs. The understanding of genome evolution during animal domestication is an interesting subject in genome biology. Dog is an excellent model for understanding of domestication due to its considerable variety of behavioral and physical traits. The Zagros area of current day Iran has been identified as one of the initial centers of animal domestication. The availability of the complete genome sequences of Iranian local canids can be a valuable resource for researchers to address questions and testing hypotheses on the dog domestication process. Data description We collected blood samples from six Iranian local canids including two hunting dogs (Saluki breed), a mastiff dog (Qahderijani ecotype) and three wolves. We extracted genomic DNA from blood samples. Sequence data were produced using the Illumina HiSeq 2500 system. All sequence data are available in the National Genomics Data Center (NGDC), Genome Sequence Archive (GSA) database under the accession of CRA001324 and the National Center for Biotechnology Information (NCBI) under the accession of PRJNA639312. The short-read sequences with the mean depth of 16X were aligned to the dog reference genome (CanFam3.1) and achieved 99% coverage of the reference assembly. The obtained information from this experiment will be useful in evolutionary biology.